2022
DOI: 10.1080/09593985.2022.2031363
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in patients with chronic stroke compared with a control group of healthy people matched by age and sex

Abstract: Pulmonary function in patients with chronic stroke compared with a control group of healthy people matched by age and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Stroke patients exhibited a restrictive PFT pattern in the study by Jung K. et al with lower spirometric values compared to controls [ 19 ] and in the study by Kimura et al, in which stroke patients with and without dysphagia had lower VCs compared to healthy participants [ 21 ]. Lista-Paz et al showed that the main lung volumes were significantly reduced in people with chronic stroke compared to healthy volunteers matched by age and sex (VC, IRV, IC, FVC, FEV 1 and PEF), as well as to their own reference values (VC, ERV, IC, FVC, FEV 1 ), results suggestive of a restrictive ventilatory defect in this population [ 25 ]. Sezer et al also found a restrictive pattern with lower FVC and FEV 1 in stroke survivors [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stroke patients exhibited a restrictive PFT pattern in the study by Jung K. et al with lower spirometric values compared to controls [ 19 ] and in the study by Kimura et al, in which stroke patients with and without dysphagia had lower VCs compared to healthy participants [ 21 ]. Lista-Paz et al showed that the main lung volumes were significantly reduced in people with chronic stroke compared to healthy volunteers matched by age and sex (VC, IRV, IC, FVC, FEV 1 and PEF), as well as to their own reference values (VC, ERV, IC, FVC, FEV 1 ), results suggestive of a restrictive ventilatory defect in this population [ 25 ]. Sezer et al also found a restrictive pattern with lower FVC and FEV 1 in stroke survivors [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results from the studies included in this review indicate that stroke patients have lower spirometric variables compared to healthy individuals and compared to normal reference values [ 12 , 17 , 19 , 20 , 21 , 23 , 25 , 31 ]. This involves mainly FEV 1 and FVC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous confounding factors that have previously shown associations with lung function and kidney function decline were identified as covariates, including demographic factors, 19 body mass index (BMI) and obesity, 20 21 exposure to vapours, gases, dust and fumes (VGDF), 21 living close to traffic, 21 drinking habits, 22 smoking status, 19 hyperuricemia, 23 dyslipidaemia 24 and various comorbidities, such as diabetes, 24 stroke, 25 cardiovascular diseases, 26 hypertension, 27 CKD, chronic lung diseases, allergy and asthma. 28 The baseline demographic and clinical characteristics were recorded through questionnaires, interviews, blood tests and physical examinations.…”
Section: Covariatesmentioning
confidence: 99%